Resistive memory 2 - Lim, Boon Wee (Nanyang Technological University, 2023)
This paper presents a study on the electrical characteristics of conductive-based resistive random-access memory (CBRAM) with Silver (Ag) top electrode (TE), Indium Gallium Zinc Oxide (IGZO), and Germanium Sulfide (GeS) as the switching layer and Indium Tin Oxide (ITO) as the bottom electrode (BE) in the metal-insulator-metal (MIM) structure. The study aims to understand the performance of the device under varying magnitudes of DC stress and to understand the reaction that occurs in the materials by analyzing the results of the MIM structure. CBRAM with a specific MIM structure has been shown to exhibit stable switching characteristics using Silver (Ag) as the top electrode (TE), Germanium Sulfide (GeS) as the insulation layer, and Platinum (Pt) as the BE. However, ITO offers advantages such as higher transparency and lower cost, which makes it a potentially attractive alternative to Pt. This study will contribute to a better understanding of the compatibility of materials used in CBRAM devices, and the potential benefits of using ITO as the BE.